1940
DOI: 10.1007/bf01261000
|View full text |Cite
|
Sign up to set email alerts
|

Über den feineren Bau des Mytiliden-Periostracum, erschlossen aus Der Optik

Abstract: In seiner Monographie der Mytiliden des Go]fes yon Neapel beschreibt LTST (1902) Mit sauren Farbstoffen (Eosin, Orange G) lassen sich die einzelnen, blaBgelblich erscheinenden Schichten --besonders nach vorausgegangener Diaphanolbehandlung --mehr oder minder stark f/£rben, mit Ausnahme

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1941
1941
1970
1970

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Early workers on the functions of the mantle margin, including List (1902) who reviewed their findings, assumed that the outer surface of the middle fold, to which the periostracum is attached, plays a major part in its secretion. This view was accepted by Field (1922), Haas (1935) and White (1937) but denied by Kessel (1944); observations by the present author agree entirely with Kessel's conclusion. The first formed and so outermost layer is very thin and is sometimes not distinguishable from the layer beneath.…”
Section: The Periostracumsupporting
confidence: 73%
See 4 more Smart Citations
“…Early workers on the functions of the mantle margin, including List (1902) who reviewed their findings, assumed that the outer surface of the middle fold, to which the periostracum is attached, plays a major part in its secretion. This view was accepted by Field (1922), Haas (1935) and White (1937) but denied by Kessel (1944); observations by the present author agree entirely with Kessel's conclusion. The first formed and so outermost layer is very thin and is sometimes not distinguishable from the layer beneath.…”
Section: The Periostracumsupporting
confidence: 73%
“…Although usually clear when unstained, it is occasionally brown, and sometimes separated from the underlying layer by tiny vacuoles. Kessel (1940) reported the secretion of a layer between the first and second reported here. It disappeared as the periostracum moved outward marginally and he concluded that its substance became consolidated, losing the distinctive acidophilic and birefringent properties which he found it to have.…”
Section: The Periostracummentioning
confidence: 63%
See 3 more Smart Citations